(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
تهدف هذه الورقة البحثية إلى دراسة مدى مساهمة القطاع الفلاحي في تحقيق التنمية الاقتصادية في الجزائر خلال الفترة 2009-2018، فقد سارعت الجزائر إلى تطوير وتدعيم القطاع الفلاحي من خلال تنفيذ برامج ومخططات تنموية منها المخطط الوطني للتنمية الفلاحية " PNDA". وتوصلت الدراسة إلى ضرورة وضع رؤية مستقبلية للبحث عن خيارات استراتيجية لقطاع المحروقات ومنها القطاع الفلاحي الذي يعتبر قطاعا حيويا في الاقتصاد الوطني ويمكن أن يكون بديلا استراتيجيا لقطاع المحروقات إذا ما توافرت الظروف المناسبة من خلال توجيه الموارد الطبيعية والبشرية والمالية وتعبئتها نحو الاستثمارات الفلاحية. كلمات دالة: تنمية اقتصادية؛ قطاع فلاحي؛ برنامج التنمية الفلاحية في الجزائر PNDA. Abstract: This research paper aims to study the extent of the contribution of the agricultural sector to the achievement of economic development in Algeria during the period 2009-2018.Algeria has accelerated the development and strengthening of the agricultural sector through the implementation of development programs and plans, including the National Agricultural Development Plan "PNDA". The study concluded that it is necessary to develop a future vision to search for strategic options for the hydrocarbon sector, including the agricultural sector, which is considered a vital sector in the national economy and can be a strategic alternative to the hydrocarbon sector if the appropriate conditions exist by directing natural, human and financial resources and mobilizing them towards agricultural investments Key words: economic development; agricultural sector; Agricultural Development Program in Algeria PNDA.